Measurement of Volatile Organic Compound Concentrations in the Exhaled Breaths of Ulcer and Non-Ulcer Samples: A Breath Profiling - Kasnawi Al Hadi; Sabila Alhadawiah; Arif Budianto; Rahadi Wirawan; Laili Mardiana (Lembaga Bale Literasi, 2026)
VOCs in exhaled breath have been shown to have diagnostic value for various respiratory diseases such as chronic obstructive pulmonary disease, asthma, and interstitial pneumonia. In diseases such as ulcers, increased levels of certain VOCs are caused by metabolic changes or abnormalities in the gut microbiome that contribute to disease symptoms. In line with this, this study aims to identify VOCs in the breath of people suffering from ulcer and non-ulcer samples (pre-clinical), using the CCS811 sensor. The methods used are clean air (calibration) and formaldehyde gas (examination) measurement inside an exposure chamber for 100 seconds. Then, the breath samples were collected and analyzed to measure the VOC concentrations. The differences in VOC concentration levels detected in breath samples in the two classifications were obtained. Breath samples from ulcer samples tend to show higher VOC concentrations than non-ulcer samples. These results show that there is a relationship between VOC concentration levels in the ulcer samples. The non-ulcer samples tends to be more stable and has lower VOC concentration levels. The increase in VOC levels is caused by changes in metabolism or abnormalities in the gut microbiome. The ANOVA results showed that there were significant differences between the ulcer and non-ulcer samples.